Milk Production in Awassi Sheep and their Crosses with Assaf under Accelerated Lambing System - Alkass, Jalal E.; AL-Azzawi, Waleed A. R.; M.AL-Tayy, Hafedh (Sulaimani Journal for Pure and Applied Sciences, 2009)
At the Sheep Breeding Station, IPA Agricultural Research Center, milk production was investigated in 92 Iraq Awassi (AW) and 95 Assaf x Awassi (AA) ewes under accelerated lambing system , together with effects of age and body weight of ewe , lambing season and sex by litter size of lamb using General Linear Model (GLM) procedure . The overall means of milk yield and lactation period were 85.64 kg and 132.36 days, respectively. AA ewes surpassed significantly AW ewes in milk yield (99.15 vs. 74.99 kg) and lactation period (139.0 vs.126.8 days).Age, weight of dam at lambing and sex by type of birth of lamb had significant effects on milk yield. Milk produced by ewes lambed at first season was significantly higher than ewes lambed during second and third season.